KAJIAN PRODUKTIVITAS TUKANG BATU TERHADAP BEBAN KERJA DAN WAKTU ISTIRAHAT PADA PEKERJAAN KONSTRUKSI BANGUNAN - Elvira Handayani; Annisaa Dwiretnani (Jurnal Civronlit Unbari, 2018)
Productivity becomes a dominant issue in the construction services industry. High productivity will result in efficient use of resources and cost savings, so that construction companies will achieve adequate profit and have a high competitiveness (competitiveness). Labor productivity can be affected by the energy it consumes and the regular schedule of rest breaks. Rest is needed to restore the physical and mental fitness of the workforce. This research was conducted on 37 masons of building construction work. The work under study is a masonry job. The results showed that age, education, and experience did not significantly affect the productivity. Break time masons, in the form of stolen breaks and management factors, quite a lot ie 1 to 6 minutes per observation (30 minutes). Based on heart rate examination, there is a decrease in productivity in the afternoon. But the mason has not been exhausted yet. So it can be concluded that the amount of break time stolen by the mason in the middle of work greatly affects the stamina of the mason.Keyword : masons, Rest time, Productivity